2018
DOI: 10.1111/ecc.12901
|View full text |Cite
|
Sign up to set email alerts
|

Fear of cancer progression in patients with stage IA malignant melanoma

Abstract: We aimed to determine the prevalence and importance of fear of cancer progression (FoP) in melanoma patients with stage IA tumours to assess psychosocial and demographic factors associated with severity of FoP and to determine the relationship of FoP and quality of life (QoL). One hundred and thirty-six patients with stage IA melanoma completed the short version of the Fear of Progression Questionnaire (FoP-Q-SF), the Hospital Anxiety and Depression Scale (HADS) and the EORTC-QLQ-C30. We found a mean FoP-Q-SF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 39 publications
4
18
0
2
Order By: Relevance
“…The expanded use of HADS allows us to compare our results with that in other dermatologic diseases and beyond. HADS-A and HADS-D scores observed for MF in this study are in the range of scores reported for severe psoriasis ( 29 ) and are partly higher than in patients with malignant melanoma stage Ia ( 50 ). In comparison with non-dermatologic diseases, the HADS results of this study are in the range of values observed in adolescents with severe asthma, coronary arteria disease, or dialysis ( 51 53 ).…”
Section: Discussionsupporting
confidence: 61%
“…The expanded use of HADS allows us to compare our results with that in other dermatologic diseases and beyond. HADS-A and HADS-D scores observed for MF in this study are in the range of scores reported for severe psoriasis ( 29 ) and are partly higher than in patients with malignant melanoma stage Ia ( 50 ). In comparison with non-dermatologic diseases, the HADS results of this study are in the range of values observed in adolescents with severe asthma, coronary arteria disease, or dialysis ( 51 53 ).…”
Section: Discussionsupporting
confidence: 61%
“…Con respecto al nivel de estudios, la presencia de más casos de ansiedad en personas con estudios medios que con estudios superiores fue coherente con investigaciones previas. Estas resaltan que un mayor nivel de instrucción permitiría tener más información con respecto a la enfermedad, disminuyendo la incertidumbre y el miedo a la misma, situación que facilita la toma de decisiones y los recursos a utilizar, favoreciendo un mejor estado emocional 19,21,22 . Finalmente, se confirma que a más edad hay menos ansiedad, consistente con otros trabajos que resaltan que una enfermedad como el cáncer implica una amenaza al proyecto de vida por la incertidumbre con respecto a su evolución, originando un mayor malestar emocional en personas de menor edad al tenerlo menos desarrollado 36,31,42 .…”
Section: Discussionunclassified
“…Cuando se analiza la actividad laboral, se indica que el mantenimiento de una vida activa se asocia a un mejor estado emocional, lo que puede estar mediado por diferentes factores como un mejor nivel económico o sentimientos de utilidad 18 . En cuanto al estado civil y al nivel educativo, se ha indicado que estar casado o tener un mayor nivel de estudios serían factores protectores frente a problemas emocionales, al favorecer la percepción de apoyo social y la disponibilidad de más recursos para hacer frente a la enfermedad [19][20][21][22] . Finalmente, respecto a la edad, algunos estudios reportan una disminución de la probabilidad de desarrollar depresión conforme aumenta 23,24 , mientras otros señalan niveles más altos de depresión y ansiedad en pacientes mayores 21,25 .…”
unclassified
“…3. Criterion validity: Based on previous studies [19], the Hospital Anxiety and Depression Scale (HADS) and the shortened version of the SF-36 Health Survey (SF-12) were used to verify the criterion validity of the AP-FOP-Q-SF.…”
Section: Determination Of Questionnaire Itemsmentioning
confidence: 99%